Idolatry and art. Emmanuel Levinas’s view - Fortis, Beniamino (International journal of philosophy and theology, 2025)
A link between art and idolatry is repeatedly asserted in the work of Emmanuel Levinas without ever being backed up by a thorough discussion. This essay aims to fill this gap by providing the argumentative support that Levinas’s reflections leave implicit. A critical reconstruction of his understanding of art and beauty, focusing on their dynamics and effects on both the objective and subjective sides, provides the basis for investigating the conception of idolatry that Levinas must imply in order for its analogy with art to be justified. Furthermore, the study also considers possible paths beyond this idolatrous paradigm, identifying potential vehicles for an anti-idolatrous development in criticism and literature. Ultimately, the article frames idolatry not as an inevitable outcome of art, but as a persistent risk, to be countered with critical and literary practices that resist closure and stimulate the responsiveness of thought.